Effectiveness of A Nutritional Instructional Program on Health-Related Outcomes for Hemodialysis Patients - Ibrahem A. Al-Ashour; Widad K Mohammed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: the study aimed to evaluate the effectiveness of a nutritional instructional program on healthrelated outcomes for hemodialysis patients through utilization of quality of life, and subjective global assessment in pretest; posttest1, posttest 2 and posttest 3.Methodology: quasi-experimental design was conducted at Al-Najaf Al–Ashraf, Specialized Center for Kidney Diseases and Transplantation. The study has been carried out during the period 1st September 2019 to 20th May 2020. The dietary instructions program constructed by researcher to measure the purpose of the study. The study sample of (76) patients referred for dialysis to the Specialized Center for Kidney Diseases and Transplantation. During the period of the study patients were selected through non-probability (purposively) and were randomly divided into two groups of (40) patients for study group and (36) patients for control group. The study group have been exposed to dietary instructional program by the researcher. The group that has not been exposed to dietary instructional program by the researcher are considered the control group. The measurement of effectiveness of dietary instructional program on patients undergoing hemodialysis through used of Quality-of-Life form and consisted of (5) main items. The subjective global assessment checklist questions and consisted of (6) items. Data was analyzed by using of descriptive data analysis (frequencies, percentages, mean, standard deviation, and graphical presentation) and by using of inferential analysis (chi-square, independent t-test, paired t-test, ANOVA test, and binominal test). Results: The results of the study demonstrated that there was non-significant difference between the study and control groups for quality-of-life score in pre dietary instructional program while; there was highly significant difference between the study and control groups for quality-of-life score in post dietary instructional program. The present study illustrated that there was non-significant difference between study and control groups in pretest at p-value (0.05), while there was highly significant difference in posttest (1,2, and 3) between study and control groups at p-value (0.05) regarding SGA.Conclusions: The study concluded that implementation instructional session will demonstrating a positive change in nutritional status and dietary habits. Difference between the two groups is due to the effectiveness of the dietary instruction program that given to the patients in the study group and not given to the control group. Recommendation: The study recommended that establishing of educational center for the patients in the hospital provided by adequate related materials, medias, audio-visuals aids and booklet for educating all patients how to cope with their medical conditions, when giving information to patients and relatives, nurses have more choices to make information clear and easily understandable